2004
DOI: 10.1007/s00244-004-0189-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Mine Tailing Accident Near Do�ana National Park (Spain) on Heavy Metals and Arsenic Accumulation in 14 Species of Waterfowl (1998 to 2000)

Abstract: This article presents the impact on waterbirds in Doñana National Park (Spain) of an accidental release of 5 million m3 acid waste produced by the processing of pyrite ore. Heavy metals (zinc, copper, cadmium, and lead) and arsenic were measured in several soft tissues (liver, kidney, and muscle) taken from 14 waterfowl species collected between April 1998 and May 2000. The main source of copper and zinc found in the waterfowl species examined was the spill waste, whereas cadmium, lead, and arsenic could also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 19 publications
7
25
2
Order By: Relevance
“…However, in some field studies, very high concentrations were reported in birds' kidneys which represent the main internal organ for the accumulation of this metal (Barjaktarovic et al 2002;Trust et al 2000). During this study, Cd showed the same pattern of accumulation in tissues as those previously established for bird tissues and organs (Gómez et al 2004;Kalisinska et al 2004;Nam et al 2005). Indeed, kidney was the main site of Cd accumulation demonstrating the role of this organ in detoxification and storage of non essential elements.…”
Section: Bioaccumulationsupporting
confidence: 67%
“…However, in some field studies, very high concentrations were reported in birds' kidneys which represent the main internal organ for the accumulation of this metal (Barjaktarovic et al 2002;Trust et al 2000). During this study, Cd showed the same pattern of accumulation in tissues as those previously established for bird tissues and organs (Gómez et al 2004;Kalisinska et al 2004;Nam et al 2005). Indeed, kidney was the main site of Cd accumulation demonstrating the role of this organ in detoxification and storage of non essential elements.…”
Section: Bioaccumulationsupporting
confidence: 67%
“…Indeed, Cd concentrations of adult birds were significantly above concentrations of Evidence of species-specific detoxification process 2357 juveniles in muscle but below juveniles in feathers. Age is one of the main factors explaining Cd accumulation, as observed in waterfowl from southern Spain (Gómez et al 2004). With continued exposure, even at low levels, Cd is accumulated throughout the life span of birds (Dailey et al 2008).…”
Section: Trace Element Distribution and Toxicity Significancementioning
confidence: 96%
“…Adults may therefore be able to deposit Cd in their plumage and subsequently eliminated it through moulting. Nonetheless in this study Cd mainly accumulated in the kidneys, which represent the major internal organ for accumulation of this non-essential element (Barjaktarovic et al 2002;Gómez et al 2004;Kojadinovic et al 2007). …”
Section: Trace Element Distribution and Toxicity Significancementioning
confidence: 98%
“…Arsenic can be solubilized in ground water, exposing animals and humans to potentially toxic effects (Nickson et al, 1998;Meharg and Hartley-Whitaker, 2002;Gó mez et al, 2004;Katz and Salem, 2005).…”
Section: Introductionmentioning
confidence: 99%